Peptides: Emerging Candidates for the Prevention and Treatment of Skin Senescence: A Review - Andrada Pintea; Andrei Manea; Cezara Pintea; Robert-Alexandru Vlad; Magdalena Bîrsan; Paula Antonoaea; Emöke Margit Rédai; Adriana Ciurba (Biomolecules)
One class of cosmetic compounds that have raised interest of many experts is peptides. The search for ingredients with good biocompatibility and bioactivity has led to the use of peptides in cosmetic products. Peptides are novel active ingredients that improve collagen synthesis, enhance skin cell proliferation, or decrease inflammation. Based on their mechanism of action, they can be classified into signal peptides, carrier peptides, neurotransmitter inhibitor peptides, and enzyme inhibitor peptides. This review focuses on the main types of peptides and their application in the cosmetic field, underlining their main limitations. One of the most significant drawbacks of cosmetic peptides is their poor permeability through membranes, which limits their delivery and effectiveness. As a result, this review follows the methods used for improving permeability through the stratum corneum. Increasing peptide bioavailability and stability for enhanced delivery to the desired site of action and visible effects have become central points for the latest research due to their promising features. For this purpose, several methods have been identified and described. Physical techniques include thermal ablation (radiofrequency and laser), electrical methods (electroporation, iontophoresis), mechanical approach (microneedles), and ultrasounds. As an alternative, innovative formulations have been developed in nano-systems such as liposomes, niosomes, ethosomes, nanoemulsions, and other nanomaterials to reduce skin irritation and improve product effectiveness. The purpose of this review is to provide the latest information regarding these noteworthy molecules and the reasoning behind their use in cosmetic formulations.